Kebutuhan Instrumen Penilaian untuk Mengukur Keterampilan Berpikir Tingkat Tinggi sesuai dengan Perkembangan Siswa Sekolah Dasar - Rukayah Rukayah (Jurnal Inovasi Pendidikan Dasar, 2019)
In the 21st century, it was required critical thinking generation which was able to solve problems and actively participate in making decisions on local and global issues that were formed through the thinking process. The research objectives were describing the questions form that are often used teachers, and the teacher’s need for assessment instruments to measure Higher-Order Thinking Skills (HOTS) that were appropriated to the level of elementary school students’ development. This was a qualitative descriptive research with a case research method. The research samples were 34 elementary school teachers in Surakarta, Central Java, Indonesia. Informant selection used snow-ball sampling technique, while the research data are elementary teachers and documents. Data collection techniques were in-depth interviews, questionnaires, and document analysis. Data validity used source and technical triangulations. Data analysis used interactive analysis techniques including of (1) data collection, (2) data reduction, (3) data presentation, and (4) conclusion. The findings showed that (1) the description questions form are most frequently used teacher and multiple choice questions only measured C1 to C4; (2) 48% of teachers needed assessment instruments that can be used to measure HOTS.